OPTIMALISASI RANCANG BANGUN MOBIL LISTRIK SEBUAH STUDI KENDARAAN HEMAT ENERGI SEBAGAI BAGIAN SOLUSI ALTERNATIF KRISIS ENERGI DUNIA - Fuad Zainuri; Asep Apriana; Dedi Dwi Haryadi (Politeknik Negeri Jakarta, 2015)
ABSTRACT Electric vehicles are one solution to the pollution problem Because the power source of electric vehicle battery or batteries are often called, that vehicles are environmentally friendly or you could say